Brill's companion to the reception of Cicero - Altman, William H. F., 1955- (Brill's Companions to Classical Reception, 2015)
Brill's Companion to the Reception of Cicero is a collection of essays by an international and interdisciplinary team of scholars that situates Cicero in the context of his use and abuse from antiquity to the present, and is intended to provide readers with several good reasons to return to the study of Cicero's writings with greater interest and respect.